Empowering Communities through SME Development: A Qualitative Study on Management Approaches - Anggie, Melanie; Werdanyaningsih, Salma (Manunggal Halim Jaya, 2024)
This qualitative study investigates community integration in Small and Medium Enterprises (SMEs) management strategies and its implications for sustainable development. The research aims to explore the management approaches employed by SMEs to engage with local communities, uncovering patterns and insights into their practices. A systematic literature review approach is adopted to gather relevant studies from scholarly databases, journals, and reports. Thematic analysis is utilized to identify recurrent themes and concepts across the literature, focusing on strategies, challenges, and implications of community integration in SMEs. The findings reveal that SMEs employ various mechanisms, including partnerships, stakeholder consultations, and inclusive decision-making processes, to engage with local communities. These initiatives aim to foster trust, collaboration, and mutual benefit, enhancing social capital and collective well-being. However, challenges such as balancing community interests with business objectives and resource constraints hinder SMEs' ability to invest in community integration efforts. Policy implications include the importance of recognizing SMEs as integral actors in community development processes and the need for creating an enabling environment to support their engagement with local communities. From a managerial perspective, SMEs should prioritize community engagement, social responsibility, and environmental sustainability to enhance their competitiveness and long-term viability. This study contributes to the understanding of community integration in SME management and highlights its significance for organizational behavior, stakeholder theory, and sustainability.